COMPARATIVE STUDY OF ETHNOMATHEMATICS LITERATURE ON WEST JAVANESE ANGKLUNG: CONSISTENCY OF THE RELATIONSHIP BETWEEN GEOMETRIC FORM AND ITS INFLUENCE ON SOUND PRODUCTION - Malika Hasana Sausan; Nurlela; Rifa Nailah Yusriani; Wahyunengsih (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
Ethnomathematics is the study of the relationship between mathematical concepts and culture. This research aims to compare findings regarding the geometric forms of West Javanese Angklung and the sound they produce when played, drawing from three previous studies. Specifically, this study investigates the consistency of the relationship between geometric forms and the resulting sound characteristics based on data presented in the studies above. The researcher uses a document analysis method to review and compare data and information related to the geometric forms of West Javanese Angklung and their sound. The research showed that the angklung's length and diameter greatly affect the sound produced when played.